Representation of Female Superhero and Gender Roles in the Avengers: Endgame - Melly Ridaryanthi; Ceaserlyn Jindan Sinuyul (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
This paper aims to present the study about the representation of female superhero characters and gender roles in Avenger: Endgame. This study is justified to be important as females usually have their stereotypical representation in mass media, including film. Thus, it is crucial to explore and analyze whether or not female superheroes are depicted similarly. There are three main characters analyzed in this movie, namely Gamora, Black Widow, and Nebula. This study applies the semiotics method with a qualitative approach whereby Roland Barthes Semiotics is employed as the theoretical foundation of the analysis and strategy in this study. The research has focused on the representation of gender roles and physical manifestations of the characters in the film. The study has shown that (i) each of the characters plays several roles based on the context of the story, (ii) the balance of power between male and female are not equally distributed, and lastly (iii) Gamora and Nebula being different species than Black Widow which is human, had their appearance interpreted to possess a human-like body, yet the pattern of body size among these three-female superheroes sends a message that this body shape is the “ideal and desirable” body type.